Implikasi Organisasi dan Sosial Manajemen Pengetahuan - Sugandi, Lianna (Humaniora, 2011)
Competitive management and organization theorists must be able to manage and publish the knowledge management concept as competitive advantages. They suggest that in order to keep on competing, the organization must efficiently and effectively create, locate, gather, and share knowledge and skills to apply knowledge in solving problems and exploiting chances. The purpose of this article is to identify that organization culture has a close relationship with knowledge management in supporting environment or situation having a high possibility of sharing knowledge. If the organization does not assume that sharing knowledge is one important thing for organization development, then the inside culture will not support knowledge sharing atmosphere.